Implementation of Gender and Development among Higher Education Institutions: Input to GAD Enhancement Program - Albaladejo, Elmer M. (JPAIR Institutional Research, 2016)
Gender and Development (GAD) is a plan for development perspective that recognizes the unequal status and situation of women and men in society. Women and men have different development needs and interests as a result of inequality, which is institutionalized and perpetuated by cultural, social, economic and political norms, systems and structures. The descriptive research investigated the facts related to GAD Implementation in HEIs using a researcher-made questionnaire. Educational managers were "very aware" of the Republic Act 7192, known as Women in Nation building implementation while faculty members were only "moderately aware". All HEIs agreed having encountered problems in GAD implementation such as inadequate trainings/seminars, lack of funding support, non-priority of GAD programs, limited collaboration of institutions on GAD-related activities, and unsustainable implementation. However, HEIs were aware that they have general and specific plans related to GAD implementation. The difference was found between educational managers and faculty members’ awareness level. Moreover, relationships were seen on the selected profile variables of HEIs and status of GAD implementation. Results of the study implied an input to GAD Enhancement program that will address the gaps for a sustainable level of implementation among HEIs.